ROLE OF BOLLYWOOD CINEMA IN PROMOTING TOURISM, BUSINESS AND INTERCULTURAL COMMUNICATION IN ARAB WORLD: A STUDY WITH OMAN - Tripathi, Sangeeta (PEOPLE: International Journal of Social Sciences, 2017)
Bollywood cinema is the replica of Indian culture purely produced for the sake of entertainment. Indian movies seem promoting intercultural communication as it shows reflection of cultural exchange from language to realm of food, music to architecture, geographical beauty to film canvas. Due to the inclusion of different countries’ cultures, Indian movies reduce the cultural shock and create a sense of closeness and warmness even in small conversations with strangers. Displayed marvelous sight scenes on big canvas of Hindi cinema attract audience and compel them to plan their vacations to that particular destination. In this way, it promotes tourism and other business in the country. The purpose of this study is to explore the threads which are vital in promoting tourism, business and intercultural communication in Arab countries. It will also examine how Bollywood cinema is influencing international audience’s subliminal mind to attract tourism and business. The paper will also discover the impact of Bollywood cinema on Omani youth and their living style. For research findings, observation and survey methods are applied. Samples are collected from different age group for variation of data to test hypotheses and get scientific result.